PELATIHAN SOFTWARE AKUNTANSI ACCURATE DALAM MENGHADAPI DUNIA KERJA DI SMA SWASTA WIYATA DHARMA MEDAN - Sulia, Sulia; Mie , Mie; Situmorang, Iskandar Muda (Universitas Methodist Indonesia, 2023)
At present, this type of business cannot be separated from calculations in financial terms, both related to capital, profits and losses. Both small, medium and large scale businesses must be related to financial and accounting issues in their management. Along with technological developments, the use of accounting software can help companies so that they can minimize errors and company productivity in terms of efficiency. But unfortunately not many schools have introduced or implemented learning about this accounting software into their curriculum, especially in high school (SMA). Accurate software is accounting software that helps to record books and makes it easier to manage financial data with the right level of accuracy in calculations. Wiyata Dharma Private High School is an educational institution with a high school level which, in carrying out its activities under the auspices of the Ministry of Education and Culture, currently has not introduced or applied knowledge regarding the use of accounting software, namely the Accurate application. So the purpose of this Community Service Activity is to provide training to students in the introduction and use of digital-based accounting applications for the process of recording business activities in the business world and increase the abilities and skills of Wiyata Dharma Medan Private High School students so they can compete in the world job after graduating from school. This training is carried out directly by applying the use of accurate applications with case studies provided by the service team. Based on the results of the answers to the training participants' questionnaires, it can be seen that there is an increased understanding of the use of accurate applications before and after training. So it can be concluded that the Training on the Use of Digital Accounting Applications (accurate applications) was successful